Diagnóstico da implantação do BIM em empresas construtoras com foco nos processos de planejamento, orçamento e controle de obras - Costa, José Martins Cavalcanti da (Universidade Federal de São Carlos, 2015)
The budget, proper planning and control play a vital role in getting profit in the current scenario in the construction sector, and the Building Information Modeling (BIM) can be a key factor in the success of businesses. This work aims to analyze the main impact of technology BIM about the planning, budgeting and control, as well as present a schematic representation of the impact of BIM on the flow of the processes studied. The methodology used in the research was the field of study, basically divided into three stages: preliminary exploration, data collection and impact on flows. Through a proposal schematisation of the flow of the processes studied, it was possible to propose details of the information exchange requirements, as well as the intensity of the impact of BIM use in each activity. In this context, it was found that the BIM platform has moderate impact in the budget, planning and control.
Diagnosis of BIM Deployment in Building Companies focusing on planning processes, Budget and Construction Control
Keywords: Building Information modeling; BIM; Orçamento; Planejamento; Controle; Budget; Planning; Control; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL